2019
DOI: 10.3390/su11041108
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Citizen Science in Conservation under the Telecoupling Framework

Abstract: Citizen science is increasingly utilized to empower people to participate in conservation work and research. Despite the profusion of citizen science projects in conservation, many lacked a coherent analytical framework for understanding broad-scale transnational human–species interactions. The telecoupling framework provides a means to overcome this limitation. In this study, we use the monarch butterfly, a migratory species of high conservation value, to illustrate how citizen science data can be utilized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
(94 reference statements)
0
10
0
2
Order By: Relevance
“…range maps and consequently help reduce uncertainty when identifying priority areas for conservation actions [65]. Citizen science data can also be used in telecoupling research to better understand large-scale people-nature interactions [66]. There is great potential to harness the same data to strengthen assessment of the impacts of human activities in space and time.…”
Section: Filling Information Gapsmentioning
confidence: 99%
“…range maps and consequently help reduce uncertainty when identifying priority areas for conservation actions [65]. Citizen science data can also be used in telecoupling research to better understand large-scale people-nature interactions [66]. There is great potential to harness the same data to strengthen assessment of the impacts of human activities in space and time.…”
Section: Filling Information Gapsmentioning
confidence: 99%
“…In this manner, a digital network of local volunteers, usually at the country level, can easily prepare their own bird distribution presence-only maps similar to our case-study demonstrated in Figure 13. This volunteered effort is prone to biases and limitations related to variability in species, time, locality, and volunteer skills [84,85]. However, spatial bias can be degraded to a certain degree using existing geospatial analytical methods [86] and consensus of the multiple automated point counts can be a natural validation method for the individual counts.…”
Section: Bird Mapping Discussionmentioning
confidence: 99%
“…D. Yang, Wan, et al. (2019) studied the environmental drivers impacting Monarch butterflies by incorporating citizen science data with the earth observation data set. Fern and Morrison (2017) modeled the critical areas for migratory songbirds by combining eBird and Landsat 8 OLI database.…”
Section: Introductionmentioning
confidence: 99%
“…One of citizen science representations-Volunteered Geographic Information (VGI) has been widely used in species distribution mapping, which facilitates the enhancement, update, and completion of many spatial data sets for research (Goodchild, 2007). D. Yang, Wan, et al (2019) studied the environmental drivers impacting Monarch butterflies by incorporating citizen science data with the earth observation data set. Fern and Morrison (2017) modeled the critical areas for migratory songbirds by combining eBird and Landsat 8 OLI database.…”
mentioning
confidence: 99%